Application Method Discussion for Increase Results Study Students' Creed of Achises on Creed Sentences Material - Lupiyanti, Nanik; Nurisdiana, Galih Wahyuli; Hanani, Nurul; Khasbulloh, Muhammad Nabil; Hidayah, Noer; Sunaiyah, Salma (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
The problem is want to be answered in this research is Can the Discussion method improve the learning outcomes of Class I students ? Moral creed subjects regarding the material of the Creed at MI Al – Islah Berbek Nganjuk Academic Year 2023/2024. In accordance with the type of research chosen, namely classroom action research, this research uses the research model from Arikunto et al. There are four activities carried out in an iterative cycle. These activities are planning, action, observation, and reflection. The steps in the next cycle are carrying out planning, action, observation And reflection Which Already revised. Before enter on cycle I done action introduction in the form of problem identification. The research instruments used in this research consisted of: Syllabus, RPP, observation sheet, instrument sheet, and formative tests. To analyze the success rate or percentage success student after process Study teach on every final The evaluation round is carried out in the form of a written test. This analysis is calculated using simple techniques, namely: (1) Assessing the results of formative exams/tests, (2) Assessing learning mastery. The research results show that student learning outcomes using Discussion have increased. This improvement can be seen through each cycle that has been carried out.